Wheelchair propulsion fatigue thresholds in electromyographic and ventilatory testing - Qi, L.; Zhang, L.; Lin, X. B.; Ferguson-Pell, M. (Spinal Cord, 2020)
Objective: The objective of the present study are physiological processes occurring when the intensity of manual wheelchair propulsion approaches levels causing muscular fatigue. In particular, we set out to (1) detect the electromyographic (EMG) and ventilatory fatigue threshold during a single wheelchair incremental test, (2) examine the relationship between EMG threshold (EMGT) and ventilatory threshold (VT), and (3) detect the EMG threshold differences between the propulsive and recovery muscle synergies. Setting: Biomechanics laboratory at the University of Alberta, Canada. Methods: Oxygen uptake and EMG signals from ten wheelchair users (seven males and three females) were recorded as they were each performing an incremental propulsion bout in their own wheelchairs on a wheelchair ergometer. The V-slope method was used to identify the VT, and the EMGT of each of the eight muscles (anterior deltoid, middle deltoid, posterior deltoid, infraspinatus, upper trapezius, sternal head of pectoralis major, biceps brachii, and triceps brachii) was determined using the bisegmental linear regression method. Results: For each participant, we were able to determine the EMGT and VT from a single incremental wheelchair propulsion bout. EMGT stands in good agreement with VT, and there was a high similarity in EMGT between push and recovery muscles (intraclass correlation coefficient = 0.91). Conclusion: The EMG fatigue threshold method can serve as a valid and reliable tool for identifying the onset of muscular fatigue during wheelchair propulsion, thus providing a foundation for automated muscle fatigue detection/prediction in wearable technology.